Religiosity and marriage : family attitudes in Croatia - Nikodem, Krunoslav (Array, 2012)
The theoretical framework of the paper, in a general sense, consists of modernization theories. As emphasized in the introduction, contemporary Croatian society is characterized by the modernization processes in the sense of the development of liberal democracy, market economy, etc. Social changes also bring about religious changes that were, due to the specificity of Croatian socio-cultural and political context, expressed first through religious revitalization and re-traditionalization. Recent insights, based on the results of empirical research, show that contemporary Croatian society is dominated by traditional forms of religiosity connected with religious institutions (institutionalized religiosity) and traditional attitudes toward marriage and family. The main hypothesis of the work is that under the influence of the modernization processes the elements of secularization, individualization and subjectivization arose in contemporary Croatian society. The work relies on those elements of the secularization theory that emphasize the decline in social significance and role of religious institutions, as well as the theories of individualization and subjectivization in the sense of the development of individualized religiosity and changes in attitudes toward marriage and family in the sense of moving away from tradition.